Towards ‘Another of Me’: Random Para Tolol :v and The Language Games - Satria, Faudyan Eka (Universitas Muhammadiyah Yogyakarta, 2019)
When social media experiences an escalation in the number of users until today, now social media offers an alternative for the community in constructing more intimate social relations. This is likened to a new world that Tom Boelstorff has tried to discuss in Second Life. Absolutely, here, the identity will find its intersection: could it reproduce? In some cases, that question turns the answer: